Mapping of citrullinated fibrinogen B-cell epitopes in rheumatoid arthritis by imaging surface plasmon resonance - van Beers, Joyce JBC (BioMed Central, 2010)
INTRODUCTION: Rheumatoid arthritis (RA) frequently involves the loss of tolerance to citrullinated antigens, which may play a role in pathogenicity. Citrullinated fibrinogen is commonly found in inflamed synovial tissue and is a frequent target of autoantibodies in RA patients. To obtain insight into the B-cell response to citrullinated fibrinogen in RA, its autoepitopes were systematically mapped using a new methodology. METHODS: Human fibrinogen was citrullinated in vitro by peptidylarginine deiminases (PAD), subjected to proteolysis and the resulting peptides were fractionated by ion exchange chromatography. The peptide composition of the citrullinated peptide-containing fractions was determined by high resolution tandem mass spectrometry. The recognition of these fractions by patient sera was subsequently analyzed by imaging surface plasmon resonance on microarrays. RESULTS: In total about two-thirds of the 81 arginines of human fibrinogen were found to be susceptible to citrullination by the human PAD2, the human PAD4 or the rabbit PAD2 enzymes. Citrullination sites were found in all three polypeptide chains of fibrinogen, although the α-chain appeared to contain most of them. The analysis of 98 anti-citrullinated protein antibody-positive RA sera using the new methodology allowed the identification of three major citrullinated epitope regions in human fibrinogen, two in the α- and one in the β-chain. CONCLUSIONS: A comprehensive overview of citrullination sites in human fibrinogen was generated. The multiplex analysis of peptide fractions derived from a post-translationally modified protein, characterized by mass spectrometry, with patient sera provides a versatile system for mapping modified amino acid-containing epitopes. The citrullinated epitopes of human fibrinogen most efficiently recognized by RA autoantibodies are confined to three regions of its polypeptides.